Analysis of effect strategies in improving water quality diarrhea prevention on Hilibala health center, South Nias district - Erisman Hondro; Sri Lestari Ramadhani Nasution; Ermi Girsang (Sean Institute, 2024)
Hilibala Community Health Center is the largest contributor to diarrhea cases, namely 662 cases. One of the causes is poor water quality. Therefore, this study aims to analyze the effect of health promotion in improving water quality to prevent diarrhea. The location of this research was carried out in the working area of the Hilibala Community Health Center, South Nias Regency. The research will start in June-August 2023. The sample in this study was 99 families and was determined using a purposive sampling formula. There were 6 informants for this research. The data was analyzed univariately, bivariately, and multivariately as well as by theme analysis. The results of the research show that there is an influence of advocacy, partnership, and community empowerment on the role of families in improving water quality as an effort to prevent diarrhea at the Hilibala Community Health Center, South Nias Regency, with the results of statistical tests obtaining a significant p-value for each, namely 0.000 < 0.05. The variable that influences this is the empowerment variable with a p-value of 0.000, OR = 9.333 (95% CI = 3.085), while the strategy used to improve water quality as an effort to prevent diarrhea at the Hilibala Health Center, South Nias Regency is to empower the community, such as working together to find clean water locations, digging wells and maintaining the cleanliness and quality of the water. This research concludes that the right strategy is to increase empowerment as a health promotion strategy in improving water quality to prevent diarrhea at the Hilibala Community Health Center, South Nias Regency. Suggestions for community health centers are to carry out situation analysis, outreach, cadre formation and intervention, and evaluation. The results of community empowerment activities with character building have a good impact, namely that the majority of people have increased understanding. The quality of life of the community will also improve as seen from the reduced number of diarrhea incidents.